2022
DOI: 10.1029/2020wr029523
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of the Scale of Representation of Heterogeneity on Simulated Salinity and Saltwater Circulation in Coastal Aquifers

Abstract: Numerical models of variable‐density groundwater flow and salt transport are a primary tool for predicting salinity distributions in coastal aquifers and estimating submarine groundwater discharge (SGD). Models are particularly useful to estimate the saline component of SGD, which can occur far offshore and is difficult to measure directly. Depending on the system and application, the level of geologic detail represented can range from homogeneous or layered to fully heterogeneous hydraulic conductivity fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 80 publications
(128 reference statements)
1
7
0
Order By: Relevance
“…We don't recommend using equivalent homogeneous models to investigate water circulations in heterogeneous aquifers. This is also demonstrated in recent studies (Michael et al, 2016;Kreyns et al, 2020;Yu and Michael, 2022). The temperature modulates density-driven circulations and influences total seawater influxes.…”
Section: Figure 12supporting
confidence: 58%
See 3 more Smart Citations
“…We don't recommend using equivalent homogeneous models to investigate water circulations in heterogeneous aquifers. This is also demonstrated in recent studies (Michael et al, 2016;Kreyns et al, 2020;Yu and Michael, 2022). The temperature modulates density-driven circulations and influences total seawater influxes.…”
Section: Figure 12supporting
confidence: 58%
“…For aquifers with randomly-distributed permeability, salinity distributions could be changed significantly under the same boundary conditions (Pool et al, 2015;Mahmoodzadeh & Karamouz, 2019). Yu and Michael (2022) applied the upscaling hydraulic conductivity methods and found that salinity distributions considering upscaling effects are completely different from the original one. However, our results suggested that the indicators of seawater intrusion varied within a relatively small range among Monte-Carlo simulations, compared with the mean value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In practice, the conditions necessary for the existence of a REV are often not met because geological media exhibit heterogeneity over a wide range of scales (Neuman and Di Federico, 2003). Errors occurring when only partially accounting for or ignoring heterogeneity generally grow with the non-linearity of the physical or chemical process under study and can result in misleading predictions (e.g., Dentz et al, 2011;Yu and Michael, 2021). For this reason, it is essential to characterize and account for the statistical properties of small-scale heterogeneity even when targeting mean properties.…”
Section: Introductionmentioning
confidence: 99%